Changes in Mental Illness Stigma in California During the Statewide Stigma and Discrimination Reduction Initiative - Collins, Rebecca L. (RAND Corporation, 2015)
Presents results of a one-year follow-up to the 2014 California Statewide Survey, which was developed to track attitudes, beliefs, and behaviors related to mental illness. This report focuses on items measuring stigma.